Aryan and Non-Aryan in India - Deshpande, Madhav M.; Hook, Peter E. (Michigan Papers On South And Southeast Asia, 2020)
In holding the January 1981 auto conference, the Center took it as their task to begin addressing the critical issues facing the industry, with particular, but not exclusive, attention to examining the role of the Japanese auto industry. They had in mind not to simply conduct a rational discussion of the trade issue but to probe the sources of Japanese competitive strength, especially those features whose study might profit them.